Regulation of revival stem cell differentiation by CREPT/RPRD1B during intestinal regeneration - Tingwei Lan; Mengdi Li; Xiaolin Duan; Huihui Jia; Yajun Cao; Yinyin Wang; Fangli Ren; Jianqiu Sheng; Junfeng Xu; Zhijie Chang (Cell & Bioscience)
Abstract Revival stem cells (revSCs) defined by transient induction of clusterin (CLU) expression rapidly expand and differentiate into multiple IEC lineages during intestinal regeneration. Although revSC induction is well-studied, the mechanisms governing their differentiation remain unclear. In this study, we demonstrate that CREPT/RPRD1B, a protein highly expressed in tumors and essential for crypt-base columnar cell (CBC) maintenance, was required for revSC differentiation during intestinal regeneration. Using Villin-Cre-mediated CREPT knockout (Vil-CREPT KO ) mice, we found that CREPT deletion leads to regeneration failure following irradiation-induced damage. Interestingly, revSCs were remarkably accumulated, but enterocytes were decreased in Vil-CREPT KO mice. Our single-cell transcriptome analyses demonstrated that CREPT deletion impaired the stem potential of revSCs and inhibited their differentiation into enterocytes and goblet cells. Lineage tracing experiments confirmed the reduced regenerative capacity of CREPT-deficient revSCs in vivo. Together, our findings identified CREPT as an important regulator of revSC differentiation during intestinal regeneration.